2022
DOI: 10.1101/2022.05.18.492419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Wnt/TCF7L1 transcriptional repressor axis drives primitive endoderm formation by antagonizing naive and formative pluripotency

Abstract: Early during preimplantation development and in heterogeneous mouse embryonic stem cells (mESC) culture, pluripotent cells are specified towards either the primed epiblast or the primitive endoderm (PE) lineage. Canonical Wnt signaling is crucial for safeguarding naive pluripotency and embryo implantation, yet the role and relevance of canonical Wnt inhibition during early mammalian development remains unknown. Here, we demonstrate that transcriptional repression exerted by Wnt/TCF7L1 promotes PE differentiati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Furthermore, in the eGRN, we identified a regulatory feedback loop between Tbx3 and Tcf7l1, which are predicted to repress each other. Tcf7l1 and Tbx3 are indeed well-known repressors in development 68,69 , but had not been directly linked to hepatocyte zonation. Our data suggests a model (Fig 6) in which the Wnt ligand is produced by endothelial cells in the central vein 70 72 has shown that inferred eGRNs can be used to predict the effect of a TF perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the eGRN, we identified a regulatory feedback loop between Tbx3 and Tcf7l1, which are predicted to repress each other. Tcf7l1 and Tbx3 are indeed well-known repressors in development 68,69 , but had not been directly linked to hepatocyte zonation. Our data suggests a model (Fig 6) in which the Wnt ligand is produced by endothelial cells in the central vein 70 72 has shown that inferred eGRNs can be used to predict the effect of a TF perturbation.…”
Section: Discussionmentioning
confidence: 99%